Prevalence of Child Maltreatment in Adults With Congenital Heart Disease and Its Relationship With Psychological Well-Being, Health Behavior, and Current Cardiac Function - Proskynitopoulos, Phileas J.; Heitland, Ivo; Glahn, Alexander; Bauersachs, Johann; Westhoff-Bleck, Mechthild; Kahl, Kai G. (Frontiers in Psychiatry, 2021)
Background: The prevalence of child maltreatment in adults with congenital heart disease (ACHD) has not been assessed so far. Child maltreatment is a major risk factor for unfavorable behavioral, mental, and physical health outcomes and has been associated with decreased quality of life. Given the increased survival time of ACHD, it is essential to assess factors that may worsen the quality of life and interact with classical cardiovascular risk factors and mental well-being. Methods: In a cross-sectional study, 196 ACHD (mean age 35.21 ± 11.24y, 44,4% female, 55.6% male) completed a thorough psychiatric and cardiac evaluation. Child maltreatment was assessed using the Childhood Trauma Questionnaire (CTQ) and rates were compared to already existing data from the German general population. Further psychological measurements included the WHO Quality of Life Question-naire, Hospital Anxiety and Depression Scale (HADS) and assessment of lifestyle factors (exercise, smoking, alcohol consumption, body mass index). To identify a relationship between current cardiac function and child maltreatment, we used lo-gistic regression. Results: ACHD reported significantly higher rates of emotional neglect and emotion-al abuse and sexual abuse and lower rates of physical neglect when compared to the general German population. In addition, total CTQ-scores, emotional abuse, emo-tional neglect, physical abuse and sexual abuse correlated with symptoms of depres-sion, anxiety, and negatively correlated with QoL. Furthermore, CTQ scores contrib-uted significantly in predicting higher New York Heart Association (NYHA) scores (p = .009). Conclusion: Child maltreatment is more common in ACHD and associated with de-creased quality of life and depression and anxiety. Furthermore, we found evidence that self-reported child maltreatment is associated with decreased cardiac function. Given the longer survival time of patients with ACHD, identifying factors that may negatively influence the disease course is essential. The negative consequences of child maltreatment may be the subject of psychosocial interventions that have demonstrated efficacy in treating posttraumatic stress disorders.